Developing Guidance on Implementing Volunteer-Led Intradialytic Arts Activities in Haemodialysis Units - Anna Wilson (MDPI AG, 2021)
The Renal Arts Group (RAG) at Queen’s University Belfast was formed in 2016 as a collaboration between patients with kidney disease, carers, clinicians, academics and artists to develop a programme of research with the ultimate aim of improving the physical and psychological quality of life of those living with kidney disease through the medium of the arts [...]